Analisis Pendapatan dan Kelayakan Usahatani Bawang Merah dengan Aplikasi Kompos Gapoktan “Bahagia Makmur” Desa Banjaratma, Bulakamba, Kabupaten Brebes - Juwanda, Muhammad; Melly Fera; Khusnul Khotimah; Reismaya Wanamertan Nugroho; Zulaikha Anugraheni (Perkumpulan Dosen Muda (PDM) Bengkulu, 2025)
Shallots are a highly sought-after vegetable commodity in Indonesia, particularly for household consumption as a flavoring agent. Analysis of income and feasibility of shallot farming in Banjaratma Village, Bulakamba District, Brebes Regency has never been studied. This study was conducted to determine the income analysis and feasibility of shallot farming conducted by farmers who are members of the